Penerapan Augmented Reality Sebagai Media Promosi Menggunakan Algoritma Regresi Logistik - Prianto, Cahyo; Harani, Nisa Hanum; Andarsyah, Roni (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Nowadays, some companies use social media to promote their product, with no exception PT. Pos Indonesia also promotes hiring an influencer to become a brand ambassador for introducing Pos and its product. In this era, digital marketing has an important influence on business. A unique way is needed to get attention and increase interaction between customers and posted content. For fulfilling that thing, a promotion app with Augmented Reality is designed. This technology combines the virtual and real world at the same time, in Indonesia itself promotion of AR is still seldom. By using AR, the PT Pos promotion package will be shown in the form of 3D objects when the Logo of PT. Pos is highlighted with Augmented Reality Camera. Then the promo could be shared using social media to emerge a bond with the user, so the user will get a poin that is managed by a logistic regression algorithm. Users will feel involved in promotion and also gain benefits in the form of poins so, indirectly there will be a lot of people who promote the product of PT. Pos voluntarily. Modeling using logistic regression is done with 1498 data, 75% of the data becomes the data train and 25% of the rest becomes the data test, the created model has an accuracy 61.07%.